Increasing Students' Interest in Science at SDN Pulau Rinca Through Science Literacy: Peningkatan Minat Siswa SDN Pulau Rinca terhadap Sains Melalui Literasi Sains - Suryani, Yani; Sulistyaningtyas, Tri; Noor, Fatimah Arofiati; Dewanti, Sira Kamila; Huljanah, Yulia Miftah (Universitas Lancang Kuning, 2025)
Abstract Rinca Island is an area in the 3T and still experiences inequality in many aspects, one of which is education. Limited access to education is shown through the condition of the school and students' knowledge about literacy and science of SDN Pulau Rinca. Unequal access makes students of SDN Pulau Rinca unable to learn science through experiments because they do not have the facilities such as the laboratory of science. This community program aims to develop science interest and reading interest of SDN Pulau Rinca students. The service was carried out by inviting students to play while learning, providing props for experiments, and providing picture books about light. The method in this service program is participatory. Students are invited to understand the phenomenon of light based on the physics point of view. The results of this service showed an increase in science interest and reading interest of SDN Pulau Rinca students. Experiments conducted with exploring games help students listen and understand the phenomenon of light well. The light phenomena taught include light can penetrate clear objects, light can be decomposed, light can be refracted, light can be reflected, and light propagates straight. Students understand the nature of light through phenomena that occur in the surrounding environment. This service also emphasizes the importance of protecting the environment to students through light experiments. Keywords: Education, Students, Teachers, Rinca Island, Literacy, Light Abstrak Pulau Rinca merupakan daerah 3T (Terdepan, Terluar, dan Tertinggal) yang masih mengalami ketimpangan dalam banyak aspek, salah satunya adalah pendidikan. Keterbatasan akses pendidikan ditunjukkan melalui kondisi sekolah dan pemahaman literasi dan sains siswa Sekolah Dasar Negeri (SDN) Pulau Rinca. Akses yang tidak merata membuat siswa SDN Pulau Rinca tidak dapat mempelajari sains melalui praktik uji coba sebab mereka tidak memiliki fasilitas yang memadai. Pengabdian masyarakat dilakukan untuk mengembangkan minat sains dan minat baca siswa SDN Pulau Rinca. Pengabdian dilakukan dengan mengajak siswa bermain sambil belajar, memberikan alat peraga untuk percobaan, dan memberikan buku bergambar tentang cahaya. Metode dalam pengabdian ini adalah partisipatoris. Siswa diajak untuk memahami fenomena cahaya berdasarkan sudut pandang fisika. Hasil pengabdian ini menunjukkan adanya peningkatan minat sains dan minat baca siswa SDN Pulau Rinca. Eksperimen yang dilakukan dengan permainan menjelajah membantu siswa menyimak dan memahami fenomena cahaya dengan baik. Fenomena cahaya yang diajarkan di antaranya cahaya dapat menembus benda bening, cahaya dapat diuraikan, cahaya dapat dibiaskan, cahaya dapat dipantulkan, dan cahaya merambat lurus. Siswa memahami sifat cahaya melalui fenomena yang terjadi di lingkungan sekitar. Pengabdian ini juga menekankan pentingnya menjaga lingkungan kepada para siswa melalui percobaan cahaya. Kata kunci: Pendidikan, Siswa, Guru, Pulau Rinca, Literasi, Cahaya